2021
DOI: 10.1097/hjh.0000000000003041
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of obstructive sleep apnoea related blood pressure surge using a novel continuous beat-to-beat blood pressure monitoring system

Abstract: Background: Obstructive sleep apnoea (OSA) episode related blood pressure (BP) surge may mediate the association of OSA with cardiovascular disease. However, BP is not measured during a clinical sleep study. Method:We tested the feasibility of incorporating the Caretaker physiological monitor, which utilizes a novel continuous beat-to-beat (b-b) BP monitoring technology, into polysomnography (PSG) and aimed to characterize BP surges related to obstructive respiratory events. B-b BP was concurrently collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…No significant differences were observed in the severity of sec-surges between SA-related and non-SA-related sec-surges (number of sec-surges: 19.5 ± 26.0 vs. 16.4 ± 29.8 events, peak: 148.2 ± 18.5 vs. 149.3 ± 19.2 mmHg, amplitude: 26.0 ± 4.3 vs. 25.8 ± 5.7 mmHg, arranged according to SA factor and non-SA factor) [ 31 ]. Our findings align with prior research, which found no significant differences between SA-related and non-SA-related BP elevation as assessed by the PTT method [ 46 ].…”
Section: Sec-surge As a New Clinical Indicatorsupporting
confidence: 92%
See 1 more Smart Citation
“…No significant differences were observed in the severity of sec-surges between SA-related and non-SA-related sec-surges (number of sec-surges: 19.5 ± 26.0 vs. 16.4 ± 29.8 events, peak: 148.2 ± 18.5 vs. 149.3 ± 19.2 mmHg, amplitude: 26.0 ± 4.3 vs. 25.8 ± 5.7 mmHg, arranged according to SA factor and non-SA factor) [ 31 ]. Our findings align with prior research, which found no significant differences between SA-related and non-SA-related BP elevation as assessed by the PTT method [ 46 ].…”
Section: Sec-surge As a New Clinical Indicatorsupporting
confidence: 92%
“…Previous studies [ 46 , 47 ] have evaluated SA-related BPV using the PTT method or pulse decomposition analysis (PDA) in patients with OSA or suspected OSA. Their SA-related BPV, nearly equal to sec-surge, was smaller than in our study.…”
Section: Sec-surge As a New Clinical Indicatormentioning
confidence: 99%